LEADING MANAGERIAL AND MANAGERIAL PERSONNEL TRAINING SYSTEM IN UZBEKISTAN DURING INDEPENDENCE YEARS (Scientific journal of the Fergana State University, 2023)
The article deals with the issues of formation of statehood on the territory of Uzbekistan, management traditions, its forms and methods, the processes of preparation and retraining of managerial personnel in the system of state administration, problems the formation of professional culture, their role in state and society development, scientific novels on historical and political-legal and research works were analyzed.